Management Practises in Finnish Manufacturing Establishments: Evidence from FMOP - Roope Ohlsbom; Mika Maliranta (The Research Institute of the Finnish Economy (ETLA), 2019)
Data collected by the recently conducted Finnish Management and Organizational Practices Survey (FMOP) by Statistics Finland is used to examine the management practices in Finnish manufacturing establishments. The FMOP project was funded by the Strategic Research Council. This paper presents the descriptive statistics, some indicative international comparisons using poststratification weighted averages and a cross-regional comparison of the large areas of Finland. The management scores appear to be only slightly behind those of the US and approximately on par with those of Germany. This suggests that the management practices in Finnish manufacturing are on a comparatively high international level. We also find evidence of cross-regional differences in management quality in Finland with aggregate (employment weighted) but not unweighted management scores, which suggests that the differences in the allocation of employment between establishments may explain regional disparities in Finland. To analyse the statistical significance of the regional disparities in workforce allocation in greater depth, we utilize a moment-based estimation procedure that allows for statistical inferences using the Olley-Pakes decomposition. We find evidence of regional variations in the policy relevant allocation component.
Keywords: D22; L25; L60; M11; M50; 330; Management practices; Management survey; FMOP; MOPS; Olley-Pakes decomposition; Competitiveness; Allocation effect; Reallocation